Avaliando o efeito de um choque de política monetária sobre o mercado imobiliário - Mario Jorge Mendonça; Luis Alberto Medrano; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article investigates the effects of monetary policy shock in the Brazilian real state market using structural VAR through the period June/2000 to August/2010. The identification is done following the agnostic procedure suggested by Uhlig (2005). The mains results are: The stock of credit to finance housing points out a drop of 2% immediately after and the industrial output of civil construction decreases strongly after this contractionary shock.
Keywords: E51; E52; 330; Geldpolitik; Wirkungsanalyse; Immobilienmarkt; Brasilien